2018
DOI: 10.1111/aas.13210
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of acute kidney injury in children after cardiac surgery

Abstract: Preoperative serum albumin level, age <12 months, preoperative pulmonary hypertension, and CPB duration were associated with risk for postoperative AKI in children who underwent congenital cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
1
24
0
2
Order By: Relevance
“…21 A retrospective study of 505 children undergoing cardiac surgery with the primary objective of determining risk factors for AKI, and its association with serum albumin levels in particular. 22 After multivariate analysis, CPB time (odds ratio [OR] ¼ 1.006, 95% confidence interval [CI] ¼ 1.003-1.009; P ¼ .002), age <12 months (OR ¼ 1.911, 95% CI ¼ 1.166-3.132; P ¼ .007), and pulmonary hypertension (OR ¼ 1.853, 95% CI ¼ 1.182-2.907; P ¼ .01) were found to be independent risk factors for AKI. Lee and colleagues found that higher preoperative albumin was associated with reduced AKI risk (OR ¼ 0.506, 95% CI ¼ 0.325-0.788; P ¼ .003).…”
Section: Acute Kidney Injury In Congenital Cardiac Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…21 A retrospective study of 505 children undergoing cardiac surgery with the primary objective of determining risk factors for AKI, and its association with serum albumin levels in particular. 22 After multivariate analysis, CPB time (odds ratio [OR] ¼ 1.006, 95% confidence interval [CI] ¼ 1.003-1.009; P ¼ .002), age <12 months (OR ¼ 1.911, 95% CI ¼ 1.166-3.132; P ¼ .007), and pulmonary hypertension (OR ¼ 1.853, 95% CI ¼ 1.182-2.907; P ¼ .01) were found to be independent risk factors for AKI. Lee and colleagues found that higher preoperative albumin was associated with reduced AKI risk (OR ¼ 0.506, 95% CI ¼ 0.325-0.788; P ¼ .003).…”
Section: Acute Kidney Injury In Congenital Cardiac Surgerymentioning
confidence: 99%
“…Lee and colleagues found that higher preoperative albumin was associated with reduced AKI risk (OR ¼ 0.506, 95% CI ¼ 0.325-0.788; P ¼ .003). 22 Furthermore, the more severe the hypoalbuminemia, the greater the risk of more severe AKI. Patients with AKI had increased pulmonary complication, re-sternotomy, ICU and hospital LOS, and days of mechanical ventilation.…”
Section: Acute Kidney Injury In Congenital Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Ao comparar as cardiopatias cianogênicas com as não cianogênicas na análise univariada foi encontrado OR 2.6 de LRA, compatível ao estudo iraniano que demonstrou ser preditor independente da ocorrência de LRA, associação também relatada nos estudos de Taylor e Wilder (AMNI et al, 2017;TAYLOR et al, 2013;WILDER et al, 2017) (ZAPPITELLI et al, 2009;LEX et al, 2014;RICCI et al, 2013 PEDERSEN et al, 2007;LI et al, 2011;TAYLOR et al, 2013). (WILDER et al, 2017;LEE et al, 2018).…”
Section: Resultsunclassified
“…Essa relação pode ser devido a menor massa muscular e pior estado nutricional desses pacientes (LI et al, 2011;AMNI et al, 2017). Ricci et al (PARK et al, 2016;LEE et al, 2018;RICCI et al, 2013 (BLINDER et al, 2012;PEDERSEN et al, 2007).…”
Section: Resultsunclassified